2009
DOI: 10.1093/aje/kwp005
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Context and Cognitive Decline in Older Mexican Americans: Results From the Hispanic Established Populations for Epidemiologic Studies of the Elderly

Abstract: In previous research on cognitive decline among older adults, investigators have not considered the potential impact of contextual variables, such as neighborhood-level conditions. In the present investigation, the authors examined the association between 2 neighborhood-context variables-socioeconomic status and percentage of Mexican-American residents-and individual-level cognitive function over a 5-year follow-up period (1993-1998). Data were obtained from the Hispanic Established Populations for Epidemiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
111
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(128 citation statements)
references
References 36 publications
9
111
2
Order By: Relevance
“…Sheffield & Peek 31 observed that socioeconomic disadvantage assessed by lower income neighborhoods was associated with a higher incidence of cognitive decline over a period of five years, whereas there was no association for social disadvantage, represented by low educational levels and lower occupational classes. The study by Al Hazzouri et al 30 also found that lower neighborhood socioeconomic status was significantly associated with a higher prevalence of cognitive decline, even after adjusting for individual schooling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sheffield & Peek 31 observed that socioeconomic disadvantage assessed by lower income neighborhoods was associated with a higher incidence of cognitive decline over a period of five years, whereas there was no association for social disadvantage, represented by low educational levels and lower occupational classes. The study by Al Hazzouri et al 30 also found that lower neighborhood socioeconomic status was significantly associated with a higher prevalence of cognitive decline, even after adjusting for individual schooling.…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies with similar objectives to this one have been carried out among older adults in Latin America (both Mexican) 30,31 . Sheffield & Peek 31 observed that socioeconomic disadvantage assessed by lower income neighborhoods was associated with a higher incidence of cognitive decline over a period of five years, whereas there was no association for social disadvantage, represented by low educational levels and lower occupational classes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 When cognitive function was followed over a five year period in 3,050 participants of the Hispanic Established Populations for Epidemiologic Studies of the Elderly, odds of incident cognitive decline decreased as a function of neighbourhood percentage of Mexican American residents and increased with neighbourhood economic disadvantage. 35 The North Staffordshire Osteoarthritis Project (NorStOP) sent individuals aged 50 and over baseline and three year questionnaires. Nineteen percent of the 3,644 people without pain interference at baseline reported it at follow-up and participants living in areas of high health deprivation had an increased risk of developing pain interference.…”
Section: Summary Of Epidemiologic Evidencementioning
confidence: 99%
“…lung, breast and colorectal cancer (Franzini & Spears, 2003, Eschbach, et al, 2005; smoking during pregnancy , infant mortality , Jenny, et al, 2001, preterm birth (Mason et al, 2010, Masi et al, 2007, and low birth weight (Masi et al, 2007, Peak & Weeks, 2002; depression (Gerst et al, 2011, Sheffield & Peek, 2009, Ostir et al, 2003; poor self-rated health (Patel et al, 2003, Shaw & Pickett, 2011; cholesterol screening ; and access to care (Haas et al, 2004). Empirical data suggest that ethnic density might work through decreased exposure to racism (Whitley et al, 2006, Becares et al, 2009) and discrimination (Whitley et al, 2006, Becares et al, 2009, Das-Munshi et al, 2010; improved social support (DasMunshi et al, 2010, Halperin & Nazroo, 2000, social cohesion (Hong et al, 2014) and social networks (Whitley et al, 2006, Becares et al, 2009, Das-Munshi et al, 2010; and increased access to care , Haas et al, 2004 and culturally appropriate resources (Whitley et al, 2006).…”
Section: Discussionmentioning
confidence: 99%